Effect of SQ 14225, an inhibitor of angiotensin I-converting enzyme, on the granulomatous response to Schistosoma mansoni eggs in mice. - Weinstock, J V (1981)
Murine schistosomiasis is a granulomatous disease associated with high serum and granuloma angiotensin I-converting enzyme (ACE) activity. SQ 14225, a specific competitive inhibitor of ACE, was administered to normal mice and mice infected with Schistosoma mansoni to determine whether this compound could inhibit granuloma ACE activity and modify the size of the granulomatous response to schistosome eggs. Peroral administration of SQ 14225 for 5 wk to infected mice with peak granulomatous responses decreased ACE activity in isolated liver granulomas. Treated mice demonstrated a decrease in granuloma size in the liver, colon, and ileum, and hydroxyproline concentration of isolated liver granulomas was increased. Mean diameters of synchronous pulmonary granulomas, induced by the pulmonary embolization of schistosome eggs into normal and sensitized mice, were decreased by a similar dose of SQ 14225. Withdrawal of SQ 14225 from unsensitized mice with 2-wk-old synchronous pulmonary granulomas induced an increase in inflammation. Infected, but not normal mice receiving SQ 14225 demonstrated reduced portal pressure, liver weight, and body weight. Both normal and infected mice experienced dipsogenesis, expanded intravascular volume, and increased serum ACE. These observations suggest that SQ 14225 can partially inhibit the granulomatous response to schistosome eggs and the pathological manifestations of schistosomiasis. It is possible that ACE has an inflammatory role in granulomatous inflammation.